2021
DOI: 10.3389/fnagi.2021.709568
|View full text |Cite
|
Sign up to set email alerts
|

The Perspective of Dysregulated LncRNAs in Alzheimer's Disease: A Systematic Scoping Review

Abstract: LncRNAs act as part of non-coding RNAs at high levels of complex and stimulatory configurations in basic molecular mechanisms. Their extensive regulatory activity in the CNS continues on a small scale, from the functions of synapses to large-scale neurodevelopment and cognitive functions, aging, and can be seen in both health and disease situations. One of the vast consequences of the pathological role of dysregulated lncRNAs in the CNS due to their role in a network of regulatory pathways can be manifested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 121 publications
(308 reference statements)
2
14
0
Order By: Relevance
“…These findings are in agreement with results of animal model's research considering NEAT1 function involving in epigenetic regulation mechanisms in AD pathology (Asadi et al, 2021[ 4 ]). Huang et al found that lncRNA NEAT1 was elevated during aging in the APP/PS1 mouse model (Huang et al, 2020[ 16 ]).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are in agreement with results of animal model's research considering NEAT1 function involving in epigenetic regulation mechanisms in AD pathology (Asadi et al, 2021[ 4 ]). Huang et al found that lncRNA NEAT1 was elevated during aging in the APP/PS1 mouse model (Huang et al, 2020[ 16 ]).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our findings showed that the plasma lncRNA BC200 level of AD patients was significantly higher than that of healthy controls. Previous research suggested that altered relative BC200 levels up-regulated in the early stages of the disease (Ahmadi et al, 2020[ 2 ]; Asadi et al, 2021[ 4 ]). Similarly, we also found high expression of BC200 in early time point in the course of AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the authors found that BC200 levels are significantly increased in the plasma of preclinical-AD subjects compared with the control group, suggesting it as promising biomarker in the early detection of the disease [ 101 ]. These findings are in agreement with previous research suggesting upregulated BC200 levels in the early stage of AD [ 106 , 107 ].…”
Section: Epigenetic Mechanismssupporting
confidence: 94%
“…Admittedly, there are still many challenges in this area that need to be overcome. Although a large number of dysregulated AD-associated lncRNAs [ 133 ] were identified, the functional characterization of most lncRNAs is still lacking, and it is a huge challenge to identify functionally important lncRNAs from multiple recorded non-coding transcripts. Thus, a comprehensive functional characterization of lncRNAs would be the logical next step.…”
Section: Discussionmentioning
confidence: 99%